Analysis of Strengthening Mechanism of the Steep Slope Embankment through Centrifugal Model Test. (14th July 2022) - Liu, Jie; Wang, Bin; Sun, Yunlong; Wang, Bin
Abstract : Centrifuge model tests were conducted to investigate the geogrid-gravelly-soil-reinforced steep slope embankments. A control experiment was carried out on a set of unreinforced embankments. The following test results were obtained. Under a centrifugal force, the unreinforced gravelly soil steep embankments failed in sudden collapse and circular sliding. By contrast, the reinforced embankments exhibited a local deformation on the slope surface and a continuous progressive deformation on the slope due to the failure of geogrid-soil interface. The geogrid reinforcement strengthened the soil and enhanced the integrity of the embankment. Thus, the stability of the slope was improved, and the horizontal lateral displacement of the slope and the settlement at the slope crest were reduced. In the design of a geogrid, reinforcements should be sparsely arranged in the upper section of the embankment and densely arranged in the lower section. For equally spaced reinforcements, the geogrid should be strengthened in the middle and lower sections of the embankment.